Efficacy and safety of the Gam-COVID-Vac in patients with immunoinflammatory rheumatic diseases: preliminary data of prospective study - A. N. Kulikov; N. V. Muravyeva; B. S. Belov; G. I. Gridneva; E. S. Aronova (Современная ревматология, 2023)
Objective: to study the efficacy and safety of the Gam-COVID-Vac vaccine in patients with immunoinflammatory rheumatic diseases (IRD) in a prospective study.Material and methods. The study included 42 patients with IRD and 57 individuals without IRD (control group) who received at least one component of Gam-COVID-Vac. Immunization with the first component of the vaccine was carried out from March 25th to August 1st, 2022, the second – 3 weeks after the first dose. On days 1, 3 and 7 after administration of the first and second components, the study participants provided information on adverse events (AEs) by telephone. All subjects were examined by a rheumatologist 1, 3 and 6 months after complete immunization. The observation period after immunization with the second dose was 6 months.Results and discussion. 42 patients received the first component of the vaccine, and 39 patients received two components. In the control group, 57 subjects were immunized with two components of the vaccine. 30–180 days after vaccination with two components of Gam-COVID-Vac, 3 (7.7%) patients were diagnosed with SARS-CoV-2 infection, which was confirmed by polymerase chain reaction. In all cases, a mild course of COVID-19 without signs of pneumonia was observed. There were no cases of COVID-19 in the control group. After immunization with the first component, a combination of at least one local and one systemic AE (SAE) was documented in 28.6% of patients with IRD and 33.3% of individuals in the control group (p>0.05). No AEs were recorded in 42.9% and 36.8% of cases respectively (p>0.05). After vaccination with the second component, a combination of ≥1 local AE and SAE was recorded in 15.4 % of patients with IRD and 22.8% of individuals in the control group (p>0.05). No AEs occurred in 71.8% and 56.1% of cases respectively (p>0.05). In 10.3% of patients with IRD and 12.3 % of those without IRD (p>0.05), a combination of local and systemic AEs was recorded after the introduction of both first and second components. No AEs were observed in 35.9% and 28.1% of cases, respectively (p>0.05). The overall rate of IRD exacerbations was 4.8%.Conclusion. Based on the available data, vaccination against COVID-19 appears to be effective and quite safe in patients with IRD.